A dynamic anode boosting sulfamerazine mineralization via electrochemical oxidation. Issue 1 (16th November 2021) - Deng, Fengxia; Xie, Jinyu; Garcia-Rodriguez, Orlando; Jing, Baojian; Zhu, Yingshi; Chen, Zhonglin; Hsu, Jyh-Ping; Jiang, Jizhou; Bai, Shunwen; Qiu, Shan
Abstract : With the aim of alleviating the rarely achieved mineralization of sulfonamide, a dynamic oxygen-vacancy-mediated TiO2 anode is designed. It allows for simultaneous high reactivity and mass transfer. Abstract : Despite numerous efforts to treat wastewater with sulfonamides, their mineralization has rarely been achieved, resulting in the generation of more toxic by-products. In this study, greater than 75% mineralization of sulfamerazine (SMR) was achieved following 4 h of electrochemical oxidation. Remarkably, the Microtox® toxicity test confirmed the elimination of by-products with higher toxicity. The electrochemical treatment process was carried out using a dynamic oxygen-vacancy-mediated TiO2 anode (TiO2 -OV@Ti-F), which comprised oxygen-deficient Ti4 O7 coated on titanium-foam (Ti-F) via thermal spraying, allowing simultaneous high reactivity and mass transfer. SMR degradation followed a pseudo-first-order kinetics model, where the rate constant ( k app = 1.64 × 10 −2 min −1 ) for the rotary TiO2 -OV@Ti-F configuration was 1.98-fold greater than that of the static one ( k app = 8.30 × 10 −3 min −1 ). This highlights the superiority of the rotary TiO2 -OV@Ti-F anode for SMR decay. The high oxidation capabilities arose from: (i) the synergetic effect between the rotating system and the Ti4 O7 coating; (ii) the enhanced mass transfer coefficient (3.49 × 10 −5 m s −1 ) in the rotating configuration, as well as the increase in SMR degradation via direct oxidation, due to a low hole injection energy, as supported by density functional theory calculations; and (iii) boosted ˙OH formation achieved via removing the gas bubbles attached to the anode, along with lower adsorption energies for H2 O and ˙OH. The results revealed that rotary TiO2 -OV@Ti-F is a promising alternative for antibiotic wastewater treatment owing to its high organic mineralization and low level of energy consumption (0.29 kW per h per gTOC).